ДИСТАНЦІЙНЕ НАВЧАННЯ ЗДОБУВАЧІВ ОСВІТИ ЗАКЛАДУ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ (Innovative professional education, 2022)
The article pays attention to distance education, the implementation ofinteractive technologies for the presentation of material, obtaining a full-fledgededucation, improving the qualifications of employees in geographically distributedplaces
Keywords: technologies, distance education, qualification, students, learning results